Using variability modelling and design patterns for self-adaptive system engineering: application to smart-home. (2015) - Berkane, Mohamed Lamine; Seinturier, Lionel; Boufaida, Mahmoud
Adaptability is an increasingly important requirement for many systems, in particular for those that are deployed in dynamically changing environments. The purpose is to let the systems react and adapt autonomously to changing executing conditions without human intervention. Due to the large number of variability decisions (e.g., user needs, environment characteristics) and the current lack of reusable adaptation expertise, it becomes increasingly difficult to build a system that satisfies all the requirements and constraints that might arise during its lifetime. In this paper, we propose an approach for developing policies for self-adaptive systems at multiple levels of abstraction. This approach is the first that allows the combination of variability with feature model and reusability with design pattern into a single solution for product derivation that gives strong support to develop self-adaptive systems in a modular way. We demonstrate the feasibility of the proposed approach with a use case based on a smart home scenario.